Hijabers: Etnografi Gaya Berhijab 5 Mahasiswa di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura - Hidayah, Dea Ummi; Arkanudin, Arkanudin; Batuallo, Ignasia Debbye (Universitas Tanjungpura, 2023)
Hijab styles and models come in various variations. The hijab, not only as a cover for the private parts but has also emerged as a form of self-expression. Muslim women who wear trendy hijabs are called hijabers. Following the hijab fashion trend that is currently happening through social media, influencers, and the surrounding environment, causes an increase in the cost of living for hijabers among students at the Faculty of Social and Political Sciences, Tanjungpura University, which is due to the increase in purchasing power to follow the hijab trend. This research aims to describe and analyze the hijabers lifestyle among students at the Faculty of Social and Political Sciences, Tanjungpura University using ethnographic qualitative research. The use of consumer behavior lifestyle theory according to Philip Kotler and Gary Armstrong is used to analyze the results of research on consumer behavior lifestyle based on motivation and resource factors. This study found that there are various styles and styles of hijab that are influenced by social media and trends, increasing the cost of living.